PENGARUH PENDAPATAN BAGI HASIL MUDHARABAH DAN BAGI HASIL MUSYARAKAH TERHADAP LABA BERSIH BANK SYARIAH - Juliana Putri; Intan Raudhatul Ma’wa (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2018)
This study aims to analyze whether the partial and simultaneous income sharing of mudharabah musharaka results in net income.The type of data used in this study is the quantitative data obtained from the monthly financial statements with a total of 48 reports. The result of the research shows that sharia financing product, which consists of revenue share of mudharabah and revenue share of musharaka to net income, this is reinforced also through result of F test indicate that F count 32,527> F table 3,209 so it can be concluded that Ho rejected and Ha is accepted which means that Mudharabah revenue sharing and revenue sharing of musyarakah variables significantly influence simultaneously to net income variable. While based on test result t which test variable by partial obtained conclusion that income variable for result of Mudharabah have significant effect to net profit of syaria bank independent and variable of revenue share of musyarakah have significant effect to net profit of Bank Syariah Mandiri. Keywords: Profit Sharing of Mudharabah, Profit Sharing of Musharaka, Net Income.